2020
DOI: 10.1093/femsec/fiaa069
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in microbial communities attached to forages with different lignocellulosic compositions in cattle rumen

Abstract: The attachment of rumen microbes to feed particles is critical to feed fermentation, degradation and digestion. However, the extent to which the physicochemical properties of feeds influence the colonization by rumen microbes is still unclear. We hypothesized that rumen microbial communities may have differential preferences for attachments to feeds with varying lignocellulose properties. To this end, the structure and composition of microbial communities attached to six common forages with different lignocell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 51 publications
7
33
0
Order By: Relevance
“…In this study, Bacteroidetes and Firmicutes were the most predominant bacterial phyla in the rumen of Tibetan sheep, corroborating the results of previous studies on Tibetan sheep (38,39), cattle (40), sheep (41), yaks (5,9,12), goats (42), and pikas (43), and indicating that these bacteria play an important role in the ecology and function of the mammalian gastrointestinal tract. Kim et al (44) conducted a meta-analysis of all selected 16S rRNA sequences stored in the NCBI database to summarize the distribution of rumen bacteria in major domestic animals and found that the proportions of Bacteroidetes and Firmicutes were approximately 31% and 56%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, Bacteroidetes and Firmicutes were the most predominant bacterial phyla in the rumen of Tibetan sheep, corroborating the results of previous studies on Tibetan sheep (38,39), cattle (40), sheep (41), yaks (5,9,12), goats (42), and pikas (43), and indicating that these bacteria play an important role in the ecology and function of the mammalian gastrointestinal tract. Kim et al (44) conducted a meta-analysis of all selected 16S rRNA sequences stored in the NCBI database to summarize the distribution of rumen bacteria in major domestic animals and found that the proportions of Bacteroidetes and Firmicutes were approximately 31% and 56%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…The majority of bacterial communities were assigned to phylum Firmicutes and Bacteroidetes, which agrees with previous studies conducted on lignocellulosic forages (Table 3) [17,[57][58][59][60]. Phylum Firmicutes dominated the bacterial community attached to barley straw (Table 3), which is consistent with Du et al (2019) [16] and explains that this phylum is the main contributor in lignocellulose degradation.…”
Section: Analysis Of Bacterial Communitysupporting
confidence: 89%
“…Thus, it causes a high total digestibility in the treatment, where it can occur because the cellulose fraction is the digestible fraction in the rumen. Gharechahi et al (2020) reported that the composition of lignocellulose, or more specifically the cellulose component, can significantly affect the availability of microbes, resulting in changes in the digestibility value of the forage. Furthermore, according to the results of a research report regarding rumen fluid testing of corn straw, it shows that changes in the composition of fiber fractions in the form of hemicellulose and cellulose in the pretreatment resulted in significant changes to the quality of the resulting fermentation (Li et al, 2017).…”
Section: Total Digestibilitymentioning
confidence: 99%